CIP's Environmental Policies Guidelines - International Potato Center (International Potato Center, 2019)
CIP’s environmental policies guidelines were formulated to reduce the levels of contamination of soil, water, air, and food products in all areas where our R&D projects are carried out. The guidelines build on CIP’s approved environmental policies as they apply to land clearing, irrigation, fertilizer use, water management, use of pesticides, and the operational procedures on distribution of vegetative material. This guidance is used to help determine possible positive or negative environmental impacts from a project’s implementation. The impacts are raised as assumptions and will depend mainly on either the intervention strategy or the adequate development of basic, applied, or adaptive research under laboratory, greenhouse, or field conditions.